Root instrumentation with an erbium:yttrium-aluminum-garnet laser: Effect on the morphology of fibroblasts - Rossa Júnior, Carlos [UNESP]; Silvério, Karina G.; Zanin, Iriana C. J.; Brugnera Júnior, Aldo; Sampaio, José Eduardo C. (My University, 2002)
Objective: The purpose of this study was to evaluate the effect of erbium:yttrium-aluminum-garnet laser instrumentation of root surfaces on the morphology of fibroblasts from continuous lineage. Method and materials: Dentinal slices with 4 mm2 of surface area were obtained from teeth extracted for severe periodontal involvement. Specimens were assigned to one of three treatment groups: group 1, application of the laser with an energy level of 250 mJ at 103 pulses per second; group 2, application of the laser with an energy level of 80 mJ at 166 pulses per second; and group 3, similar to group 2, but with concomitant water irrigation of the device. The specimens were incubated in multiwell plates containing cell culture media. After 24 hours, the specimens were submitted to routine preparation for scanning electron microscopy. Three independent and blind examiners used photomicrographs to evaluate the morphology of the fibroblasts: 0 = without cells; 1 = flat cells; 2 = round cells; and 3 = combination of round and flat cells. Results: Statistical analysis indicated that there were significant differences among treatment groups and that group 3 was significantly different from groups 1 and 2. Conclusion: There was no difference between groups 1 and 2 in the morphology of fibroblasts. Laser instrumentation with concomitant irrigation impaired the adhesion of fibroblasts to dentinal surfaces.
Keywords: Fibroblast; Laser; Periodontal disease; Periodontal therapy; Tooth root; aluminum silicate; erbium; water; yttrium; cell adhesion; cell lineage; cell size; clinical trial; controlled clinical trial; controlled study; culture technique; fibroblast; human; laser surgery; lavage; methodology; nonparametric test; observer variation; pathology; periodontal ligament; randomized controlled trial; scanning electron microscopy; single blind procedure; statistics; tooth root; Aluminum Silicates; Cell Adhesion; Cell Culture Techniques; Cell Lineage; Cell Size; Erbium; Fibroblasts; Humans; Irrigation; Laser Surgery; Microscopy, Electron, Scanning; Observer Variation; Periodontal Ligament; Single-Blind Method; Statistics; Statistics, Nonparametric; Tooth Root; Water; Yttrium